‘Social Gap’ on Chinese Loanwords Motivation in KBBI: A Response to Zenner et al (2019) - Sophia Kardiana Bertha Sugiarto; Ika Nurhayani; Ismatul Khasanah (CV. Syntax Corporation Indonesia, 2025)
This study is motivated by the absence of application in specific language contact areas, which creates a gap in the study of social motivation as highlighted by Zenner et al. The research aims to identify the ‘social gap’ in the absorption of Chinese loanwords in the KBBI from the perspective of employees at PT. Indonesia Technical Machinery, as well as to analyze absorption patterns using the approach employed by Zenner et al. (2019) to address this gap. This approach refers to the four main theories of Zenner et al. (2019): Social Meaning, Social Identity, Indexicality, and Language Regard, with the benefit of enriching the understanding of social motivation in the process of lexical borrowing. This study analyzes 117 data points using a triangulation method involving questionnaires, comparisons, and literature studies. The data were analyzed through reduction, verification, and presentation using a thematic analysis approach to identify patterns of lexical absorption. The study results reveal the patterns represented by (BE-0-1-D-1-0) and (AD-0-1-D-1-0), with the following explanation: influenced by cultural and environmental backgrounds; not dependent on social strata, occupation, or societal dominance; not influenced by the intended impact of speakers on interlocutors; supporting divergence; non-indexical in nature; and positively perceived.